PENGARUH MODEL CONNECTING, ORGANIZING, REFLECTING, EXTENDING (CORE) TERHADAP KEMAMPUAN KONEKSI DITINJAU DARI KEMAMPUAN AWAL MATEMATIS - Esih Sukaesih; Hepsi Nindiasari; Abdul Fatah (Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to explain the effect of connecting, organizing, reflecting, extending (CORE) models on connection skills reviewed based on students' initial mathematical abilities. This study is a true experimental study using the Randomized Pretest-Posttest Control Group Design research design with a population of class XI IPA in Ciomas 1 High School. The instrument used in this study was the description test to measure students' mathematical connecation skills. The hypothesis of this study was tested using the Two Way ANNOVA test. From the results of completing the student description test, it was found that: (1) Mathematical connection skills of students who obtained learning with the Connecting, Organizing, Reflecting, Extending (CORE) models were no better than students who obtained scientific learning; (2) Connection skills of students who have high initial mathematical abilities are no better than students who have low mathematical initial abilities; (3) Mathematical connection skills of students who obtain learning with the Connecting, Organizing, Reflecting, Extending (CORE) model are no better than students who obtain scientific learning in terms of KAM as a whole; and (4) There is no interaction between the learning model and students 'initial mathematical abilities (high, medium and low) to the students' mathematical connecation skills.